Implications of Glacial Melt-Related Processes on the Potential Primary Production of a Microphytobenthic Community in Potter Cove (Antarctica) - Hoffmann, Ralf; Al-Handal, Adil Yousif; Wulff, Angela; Deregibus, Dolores; Zacher, Katharina; Quartino, María Liliana; Wenzhöfer, Frank; Braeckman, Ulrike (Frontiers in Marine Science, 2019)
The Antarctic Peninsula experiences a fast retreat of glaciers, which results in an increased release of particles and sedimentation and, thus, a decrease in the available photosynthetic active radiation (PAR, 400–700 nm) for benthic primary production. In this study, we investigated how changes in the general sedimentation and shading patterns affect the primary production by benthic microalgae, the microphytobenthos. In order to determine potential net primary production and respiration of the microphytobenthic community, sediment cores from locations exposed to different sedimentation rates and shading were exposed to PAR of 0–70 μmol photons m–2 s–1. Total oxygen exchange rates and microphytobenthic diatom community structure, density, and biomass were determined. Our study revealed that while the microphytobenthic diatom density and composition remained similar, the net primary production of the microphytobenthos decreased with increasing sedimentation and shading. By comparing our experimental results with in situ measured PAR intensities, we furthermore identified microphytobenthic primary production as an important carbon source within Potter Cove’s benthic ecosystem. We propose that the microphytobenthic contribution to the total primary production may drop drastically due to Antarctic glacial retreat and related sedimentation and shading, with yet unknown consequences for the benthic heterotrophic community, its structure, and diversity.